Agency Theory in Measuring Company Performance From the Perspective of Sharia Issuers - Dwi Astutik; Galuh Aditya; Sudarman Sudarman; Deny Nitalia Mindrawti; Hani Krinawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Purpose: direct significance test of institutional and managerial ownership and independent board of commissioners on company performance. Method: through a quantitative approach with a population of 70 companies JII70 in 2021-2023, data was determined based on purposive sampling of 144 data processed, analyzed by regression. Results: Institutional ownership and independent board of commissioners proved to be significant in the same direction in growing company performance, but managerial ownership had no impact or contradicted agency theory. Future research: adding other determinants of company performance from both micro and macro perspectives.